Disparity of learning styles and higher order thinking skills among technical students - Yee , Mei Heong (Elsevier Ltd., 2015)
Learning styles and higher order thinking skills are an important aspect in teaching and learning especially at higher education institutions. The purpose of this research was to analysis the disparity in learning styles on the level of higher order thinking skills (HOTS) among technical students. A total of 375 technical students from four technical universities in Malaysia were randomly selected as samples. The Kolb Learning Styles Inventory and a set of questionnaires adapted from Marzano Rubrics for Specific Task or Situations were used as research instruments. This is a quantitative research and the gathered data was analyzed using SPSS software. The findings indicated that the most dominant learning style among technical students is Doer. The findings also depict none of the students perceived their thinking skills’ levels to be high. Only four Marzano HOTS, namely comparing, inductive reasoning, deductive reasoning and investigation are rated at the moderate level. On contrary, nine Marzano HOTS are rated as low. The Cramer V analysis showed that there is a very low relationship between Kolb Learning Styles and the level of 13 Marzano HOTS. Besides that, the findings revealed that there is statistically significant difference in Kolb Learning Styles on the level of 13 Marzano HOTS. However, only two Marzano HOTS are significant difference in Kolb Learning Styles. Therefore, the identification of learner’s learning styles could serve as initial guide in developing more effective and conducive teaching-learning environment for learning HOTS.